The legend of Saint Aūr and the monastery of Naqlūn : the Copto-Arabic texts - Hacken, Clara ten (Clara Elisabeth) (Eastern Christian studies, 2019)
This book studies the literary heritage of the Coptic Orthodox monastery of the Archangel Gabriel at Naqlūn in the Fayyum province in Egypt by focusing on the hagiographical cycle of Saint Aūr, the presumed founder of its church. It presents the edition and translation, with extensive commentaries, of six previously unedited texts, all preserved in Middle Arabic. The author argues that the literary tradition around the monastery of Naqlūn evolved in about the eleventh century, a period in which the monastery experienced a revival. The texts recall the memory of great saints from the past, among whom Saint Antony, and convey a new view of the Christian landscape of this region. -- Backside cover.